Answer:
C. –120a2b2c2
Step-by-step explanation:
We'll just the multiplications one at a time...
10ac × 6ab × (–2bc) = 60a²bc * (-2bc) (multiplying 10ac × 6ab)
60a²bc * (-2bc) = -120a²b²c²
We just have to multiply the numbers together (like 10 and 6),
then all similar letters together (like ac * ab = a²bc). If a letter is already present (like a in this example), then we add up its powers a * a = a², a² * a would be a³ and so on). If the letter is not present (like 'b' in 'ac', we suppose it's there as b^0 which is equal to 1)... so we still add up its exponent (power)... so it makes b^0 * b = b